Sistem Pendukung Keputusan Pemilihan Mobil Bekas dengan Metode AHP dan SAW pada Nava Sukses Motor - Irawan Setiadi (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2019)
Someone buying a used vehicle in determining his choice, of course, is based on several criteria that are used as a benchmark in choosing used car vehicles, including engines, body, interior, frame number & engine, letters & taxes, and prices. These criteria are a consideration for buying a used car, various considerations are made by a buyer to get a good and good used car. Difficulties in choosing a used car, a reference is needed as a rationale for choosing a used car. Decision support systems offer a solution for referrals in choosing a used car. Decision support systems offered using Analytical Hierarchy Process (AHP) and Simple Additive Weighting (SAW) in solving problems. Problems can be solved using a ranking system based on global weighting. Buyers of used car vehicles can choose used cars based on references or recommendations from expert decision support systems. Based on the results of the calculation of the assessment criteria proposed to the system, the determination of used cars is obtained through calculating the priority weight values for the selection of used cars to be purchased. With the Decision Support System to choose used cars using the Analytical Hierarchy Process (AHP) method and Simple Additive Weighting (SAW) in determining used cars the accuracy rate is 73% compared to using the Simple Additive Weighting (SAW) method which has a level of accuracy only 60%.